Exploring the Influence of Behavioral Nudging on Adaptive Leadership Perceptions Among Doctoral Students in High-Pressure Academic Environment - Moses Adeleke Adeleke (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
In the rapidly evolving landscape of higher education, the need for effective leadership among doctoral students has become increasingly critical. This research study explores the perceptions of adaptive leadership and the impact of behavioural nudging strategies among postgraduate students in educational management at two private universities in Nigeria. Employing a mixed-methods research design, the study addressed three key research questions and involved 58 participants. The findings revealed that participants acknowledged the importance of adaptive leadership, scoring an average of 4.12 in relevance, yet expressed moderate confidence in their adaptive leadership abilities (mean score of 3.60). Regarding behavioural nudging, participants reported a favourable view of its effectiveness (mean score of 3.45). Still, they stressed the necessity for integrating these strategies with robust support systems, such as mentorship and institutional resources. Key challenges identified included limited resources, inadequate mentorship, and time management issues, which hindered their leadership development. In conclusion, while there is a strong recognition of the significance of adaptive leadership and nudging strategies, systemic barriers remain. The study recommends implementing comprehensive leadership development programs, enhancing mentorship opportunities, integrating nudging strategies into academic support, fostering collaborative learning environments and conducting ongoing research to evaluate the effectiveness of these initiatives. By addressing these recommendations, educational institutions can better equip doctoral students with the adaptive leadership skills necessary to navigate the complexities of their academic and professional journeys.